The arrival of the ACEs movement in Scotland: Policy entrepreneurship and critical activist responses. Issue 4 (November 2020) - Walsh, Gary M.
Abstract : This paper combines conceptual and documentary analysis to critique the recent introduction of ACEs (Adverse Childhood Experiences) in Scottish social policy, highlighting the role of the ACE-Aware Nation 'movement' and its positioning of the ACEs model through its campaigning activities. Consideration is given to the role of a sophisticated network of policy entrepreneurs and the commercial and political interests at play. Reflection is offered on the critical activist responses to this campaign that seek to highlight the socio-economic and political underpinnings of childhood trauma, which are largely absent in the ACEs model. The argument is that these policy developments amount to a recent turn to the ACEs model as a simplistic solution to complex social problems – a solution that is shown to be ultimately flawed in several respects. This analysis reveals the contradictions, conflicts and confusion that have emerged within the ACEs discourse, caused in the main by heuristic thinking and the conceptual inadequacies, misuses and misunderstandings of the ACEs model. The paper concludes that policy makers and practitioners should exercise caution in their appraisal of the ACEs model and the associated movement in Scotland.